Participation and Diffusion Effects of a Peer-Intervention for HIV Prevention among Adults in Rural Malawi - Crittenden, Kathleen S. (Soc Sci Med, 2015)
This paper examines whether a peer group intervention that reduced self-reported risky behaviors for rural adults in Malawi also had impacts on non-participants in the same communities. We randomly assigned two districts to the intervention and control conditions, and conducted surveys at baseline and 18 months post-intervention using unmatched independent random samples of intervention and control communities in 2003-2006. The six-session peer group intervention was offered to same-gender groups by trained volunteers. In this analysis, we divided the post-intervention sample into three exposure groups: 243 participants and 170 non-participants from the intervention district (total n=415) and 413 control individuals. Controlling for demographics and participation, there were significant favorable diffusion effects on five partially overlapping behavioral outcomes: partner communication, ever used condoms, unprotected sex, recent HIV test, and a community HIV prevention index. Non-participants in the intervention district had more favorable outcomes on these behaviors than survey respondents in the control district. One behavioral outcome, community HIV prevention, showed both participation and diffusion effects. Participating in the intervention had a significant effect on six psychosocial outcomes: HIV knowledge (two measures), hope, condom attitudes, and self-efficacy for community HIV prevention and for safer sex; there were no diffusion effects. This pattern of results suggests that the behavioral changes promoted in the intervention spread to others in the same community, most likely through direct contact between participants and non-participants. These findings support the idea that diffusion of HIV-related behavior changes can occur for peer group interventions in communities, adding to the body of research supporting diffusion of innovations theory as a robust approach to accelerating change. If diffusion occurs, peer group intervention may be more cost-effective than previously realized. Wider implementation of peer group interventions can help meet the global goal of reducing new HIV infections.